CSR signaling in controversial and noncontroversial industries: CSR policies, governance structures, and transparency tools. Issue 2 (April 2023) - Conte, Francesca; Sardanelli, Domenico; Vollero, Agostino; Siano, Alfonso
Abstract: Corporate social responsibility (CSR) initiatives are signals used by organizations to reduce information asymmetries within the market and to make their commitment to sustainability observable. The present study aims at investigating the hypothesis that responsible companies operating in controversial industries (i.e., companies whose core business or production processes are perceived as questionable by society given current environmental, social, or/and ethical issues) are likely to be more active in using different types of CSR signals. Through ANCOVA, we assess how firms belonging to both controversial and non-controversial industries differ in the way they manage CSR signals. The empirical results show that companies in controversial sectors are significantly more focused on developing CSR policies and transparency tools since they expect these signals to be really visible and distinctive to stakeholders. However, companies in controversial industries seem to be similar to non-controversial companies in signaling CSR governance, suggesting that organizations expect receivers to attribute little relevance to the least visible signals. Therefore, these signals do not grant a sufficiently large reputational payoff, discouraging firms from taking advantage of the implementation of CSR governance structures. The study supports the idea that firms, in designing different types of CSR signals, take into account the peculiarities of different receivers. At the same time though, this could make firms underestimate the receivers' ability to decode the signals and to generate countersignals, thus failing in assessing properly the expected return from their CSR signaling.